Associations between the Geriatric-8 and 4-meter gait speed test and subsequent delivery of adjuvant chemotherapy in older patients with colon cancer. Issue 8 (November 2021) - Beukers, K.; Bessems, S.A.M.; van de Wouw, A.J.; van den Berkmortel, F.W.P.J.; Belgers, H.J.; Konsten, J.L.M.; Sipers, W.M.W.H.; Janssen-Heijnen, M.L.G.
Abstract: Objectives: Feasible screening methods are important to identify older patients who might benefit from adjuvant chemotherapy. The aim of this study was to investigate the associations between the outcomes of screening for frailty with the Geriatric-8 questionnaire (G8) and the 4-meter gait speed test (4MGST) and subsequent delivery of adjuvant chemotherapy and treatment tolerance in older patients with colon cancer. Material and Methods: This retrospective multicentre study included all patients aged ≥70 with primary colon carcinoma who underwent elective surgery between May 2016 and December 2018 and for whom adjuvant chemotherapy was indicated. Data were analysed using multivariate regression models. Results: 97 (73.5%) of 132 eligible patients were screened by the G8 and 85 (64.4%) by the 4MGST. In univariate analyses, patients who scored indicative for frailty on both the G8 (≤14) and the 4MGST (>4 s) significantly more often did not proceed with adjuvant chemotherapy than patients who scored fit on both instruments (OR = 5.10, p = 0.01). After adjustment for gender, stage, and postoperative complications, the OR decreased to 4.22 ( p = 0.04). Tolerance of treatment was very high (93%) and did not differ between screening groups. Conclusion: Although patients who scored indicative for frailty on both the G8 and the 4MGST significantly more often did not proceed with adjuvant chemotherapy, it is still unknown whether the G8 and the 4MGST are reliable tools for identifying patients who are at high risk for severe chemotoxicity. Nonetheless, this study shows that current selection for adjuvant chemotherapy among older patients with colon cancer is safe with low rates of severe chemotoxicity.